Analysis of the causes and consequences of accidents occurring in two constructions projects (2023)
Work done on construction sites is considered to be high risk, resulting in instances of occupational accidents that impact the physical, mental and social integrity of the workers as well as company productivity. Therefore, the objective of this article is to analyze the causes and consequences of occupational accidents occured in the second semester of 2012 in two construction projects in Neiva, Colombia. The approach is documentary, supported by information sources of occupational accidents reported to the Administration of Occupational Accidents (ARL in Spanish); the model developed by Frank E. Bird was used to determine the causes of these accidents. A total of 117 accidents were analyzed, detecting 195 failures of control, 136 personal factors, 112 work related factors, 151 unsafe acts and 54 unsafe conditions; some accidents had more than one cause. In this manner, the authors conclude that the largest percentage of occupational accidents were caused by lack of control, followed by unsafe acts. Therefore, the use of programs of risk management priorities is recommended, based on the proper identification of hazards, allowing the mitigation and control of risk; likewise developing a culture of self-care in workers is recommended.